2018
DOI: 10.1007/s11936-018-0675-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the Postsurgical Aorta in Marfan Syndrome

Abstract: Marfan syndrome is a heritable multisystem connective tissue disease and is the most common genetic cause of aortic disease. Guidelines for surgical repair and recommendations for surveillance imaging aim to prevent aneurysm rupture, aortic dissection, and death. Options for proximal aorta repair include the modified Bentall procedure and valve-sparing aortic root repairs. Hemiarch and total arch replacement are options for aortic arch repair, and the elephant trunk procedure is a special two-staged total arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…MR angiography (MRA) is performed every 6 months to monitor the morphologic change of the aorta. Although special resolution and examination time are inferior to CT, MRA does not utilize ionizing radiation, so it may be better in young patients with Marfan syndrome requiring frequent postsurgical image surveillance . We propose that the reported management strategy can prevent aortic complications in patients undergoing orthotopic heart transplantation with CTD, without subjecting them to the increased morbidity of extensive prophylactic aortic reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…MR angiography (MRA) is performed every 6 months to monitor the morphologic change of the aorta. Although special resolution and examination time are inferior to CT, MRA does not utilize ionizing radiation, so it may be better in young patients with Marfan syndrome requiring frequent postsurgical image surveillance . We propose that the reported management strategy can prevent aortic complications in patients undergoing orthotopic heart transplantation with CTD, without subjecting them to the increased morbidity of extensive prophylactic aortic reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic aortic root replacement is often considered at the time of AVR in patients with aortopathy to mitigate the risk of future aortic dissection. The Modified Bentall procedure is the standard technique, consisting of a synthetic ascending aorta and root graft with a bioprosthetic or mechanical valve (68). A large study has demonstrated the low rate of long-term aortic complications with this technique (69).…”
Section: Aortic Root Replacementmentioning
confidence: 99%
“…Systolic flow vortices in the Sinus of Valsalva (SOV) occur after peak systole and persist until diastole and are thought to have an important role in valve closure and coronary perfusion ( Figure 5) (75). Valve-sparing aortic root replacement, by either the David or Yacoub technique, involves excision of the native Sinus of Valsalva (68). This loss of sinus architecture abolishes vortical flow and may have longer term consequences.…”
Section: Valve-sparing Aortic Root Replacementmentioning
confidence: 99%
“…Extra-aortic aneurysms and dissections are most commonly noted as a consequence of aortic dissection, in which the dissection extends to more distal vessels [119,121,[125][126][127]. Less well characterized are aneurysms and dissection of the peripheral vessels independent of aortic dissection.…”
Section: Aneurysm and Dissection Of Large-and Mediumsized Arteriesmentioning
confidence: 99%
“…In Marfan syndrome, the visceral arteries are most commonly involved after descending aortic dissection or graft repair, when the visceral arteries are at risk of dissection and patch aneurysm [127]. Rare cases of visceral artery aneurysms unrelated to dissection have also been reported in Marfan syndrome including in the gastric, celiac artery, splenic, and hepatic arteries, almost all necessitating intervention [120,121,125,137,[165][166][167].…”
Section: Visceral Arteriesmentioning
confidence: 99%